A Propensity Score–weighted Comparison of Outcomes Between Living and Standard Criteria Deceased Donor Kidney Transplant Recipients. Issue 11 (November 2020) - Yohanna, Seychelle; Naylor, Kyla L.; McArthur, Eric; Lam, Ngan N.; Austin, Peter C.; Habbous, Steven; McCallum, Megan K.; Ordon, Michael; Knoll, Greg A.; Kim, Joseph S.; Garg, Amit X.
Abstract : Background: Consider a theoretical situation in which 2 patients with similar baseline characteristics receive a kidney transplant on the same day: 1 from a standard criteria deceased donor, the other from a living donor. Which kidney transplant will last longer? Methods: We conducted a population-based cohort study using linked administrative healthcare databases from Ontario, Canada, from January 1, 2005, to March 31, 2014, to evaluate several posttransplant outcomes in individuals who received a kidney transplant from a standard criteria deceased donor (n = 1523) or from a living donor (n = 1373). We used PS weighting using overlap weights, a novel weighting method that emphasizes the population of recipients with the most overlap in baseline characteristics. Results: Compared with recipients of a living donor, the rate of all-cause graft failure was not statistically higher for recipients of a standard criteria deceased donor (hazard ratio, 1.1; 95% confidence interval [CI], 0.8-1.6). Recipients of a standard criteria deceased donor, compared with recipients of a living donor had a higher rate of delayed graft function (23.6% versus 18.7%; odds ratio, 1.3; 95% CI, 1.0-1.6) and a longer length of stay for the kidney transplant surgery (mean difference, 1.7 d; 95% CI, 0.5-3.0). Conclusions: After accounting for many important donor and recipient factors, we failed to observe a large difference in the risk of all-cause graft failure for recipients of a standard criteria deceased versus living donor. Some estimates were imprecise, which meant we could not rule out the presence of smaller clinically important effects. Abstract : Supplemental Digital Content is available in the text.